Acceptability of Nurse-Driven HIV Screening for Key Populations in Emergency Departments: A Mixed-Methods Study. Issue 5 (September 2021) - Leblanc, Judith; Côté, José; Auger, Patricia; Rouleau, Geneviève; Bastide, Théophile; Piquet, Hélène; Fromentin, Hélène; Jegou, Carole; Duchêne, Gaëlle; Verbrugghe, Rachel; Lancien, Cécile; Simon, Tabassome; et al.
Abstract : Background: Optimizing care continuum entry interventions is key to ending the HIV epidemic. Offering HIV screening to key populations in emergency departments (EDs) is a strategy that has been demonstrated to be effective. Analyzing patient and provider perceptions of such screening can help identify implementation facilitators and barriers. Objectives: The aim of this study was to investigate the acceptability of offering nurse-driven HIV screening to key populations based on data collected from patients, nurses, and other service providers. Methods: This convergent mixed-methods study was a substudy of a cluster-randomized two-period crossover trial conducted in eight EDs to evaluate the effectiveness of the screening strategy. During the DICI-VIH (Dépistage Infirmier CIblé du VIH) trial, questionnaires were distributed to patients aged 18–64 years. Based on their responses, nurses offered screening to members of key populations. Over 5 days during the intervention period in four EDs, 218 patients were secondarily questioned about the acceptability of screening. Nurses completed 271 questionnaires pre- and posttrial regarding acceptability in all eight EDs. Descriptive analyses were conducted on these quantitative data. Convenience and purposeful sampling was used to recruit 53 providers to be interviewed posttrial. Two coders conducted a directed qualitative content analysis of the interview transcripts independently. Results: The vast majority of patients (95%) were comfortable with questions asked to determine membership in key populations and agreed (89%) that screening should be offered to key populations in EDs. Nurses mostly agreed that offering screening to key populations was well accepted by patients (62.2% pretrial and 71.4% posttrial), was easy to implement, and fell within the nursing sphere of competence. Pretrial, 73% of the nurses felt that such screening could be implemented in EDs. Posttrial, the proportion was 41%. Three themes emerged from the interviews: preference for targeted screening and a written questionnaire to identify key populations, facilitators of long-term implementation, and implementation barriers. Nurses were favorable to such screening provided specific conditions were met regarding training, support, collective involvement, and flexibility of application to overcome organizational and individual barriers. Discussion: Screening for key populations was perceived as acceptable and beneficial by patients and providers. Addressing the identified facilitators and barriers would help increase screening implementation in EDs. Abstract : Supplemental digital content is available in the text.